1998
DOI: 10.1152/ajpregu.1998.275.1.r194
|View full text |Cite
|
Sign up to set email alerts
|

Role of ANG II in mediating somatosensory-induced renal nerve-dependent antinatriuresis in the rat

Abstract: This study examined the renal nerve-dependent renal hemodynamic and tubular responses to somatosensory stimulation in the anesthetized rat by use of subcutaneously applied capsaicin when the action of ANG II was blocked peripherally or selectively within the brain. Activation of skin somatosensory receptors caused a transient reversible 10–15% increase in blood pressure, and while renal perfusion pressure was regulated at control levels, there was a transient fall in urine flow and sodium excretion even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
5
16
0
Order By: Relevance
“…We have previously reported 6 that in this situation the capsaicin acts to depolarize the subcutaneous nociceptors, 16 giving rise to a somatosensory input, thus causing a reflex increase in renal sympathetic nerve activity and a renal nerve-mediated antidiuresis and antinatriuresis. 10 The present study supports this view in that the somatorenal reflex was intact in the Wistar rats. It was also clear that this somatosensory-mediated reflex neural control of urinary flow and sodium excretion was dependent on Ang II in the brain, as following blockade of its receptors with intracerebroventricular losartan, the excretory responses were prevented.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We have previously reported 6 that in this situation the capsaicin acts to depolarize the subcutaneous nociceptors, 16 giving rise to a somatosensory input, thus causing a reflex increase in renal sympathetic nerve activity and a renal nerve-mediated antidiuresis and antinatriuresis. 10 The present study supports this view in that the somatorenal reflex was intact in the Wistar rats. It was also clear that this somatosensory-mediated reflex neural control of urinary flow and sodium excretion was dependent on Ang II in the brain, as following blockade of its receptors with intracerebroventricular losartan, the excretory responses were prevented.…”
Section: Discussionsupporting
confidence: 89%
“…In our previous studies, we had shown that Ang II in the brain was necessary to allow a somatosensory-induced renal nerve-dependent antidiuresis and antinatriuresis to take place. 10,11 Indeed, this would be consistent with the observations of Sasaki and Dampney 14 and Hirooka and Dampney, 15 who showed that Ang II elicited an excitatory action at the rostral ventrolateral medulla, an important nucleus involved in determining sympathetic outflow, and appeared to have a facilitatory role in allowing somatosensory stimulation to elicit an increase in sympathetic outflow to the periphery. However, it was also evident that this somatosensory-mediated reflex neural control of sodium excretion was blunted in the SHRSP, 9,12 but whether this was due to a deficit within the brain or at the neuroeffector sites within the kidney was not clear.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Male Wistar rats (300-350 g) were placed into a stereotaxic frame and drugs were administered into the right lateral cerebroventricle [14]. For this purpose, a guide cannula, made up of stainless steel tubing (0.82 mm diameter) was placed at the site 1.0 mm posterior to the bregma, 2.5 mm lateral to midline and 2.55 mm ventral to the surface of the dura.…”
Section: Rat Preparationsmentioning
confidence: 99%